Analysis and Design of Decision Support System for Employee Performance Appraisal with Simple Additive Weighting (SAW) Method - Taufiq, Rohmat; Septarini, Ri Sabti; Hambali, Ahmad; Yulianti, Yulianti (Jurnal Informatika Universitas Pamulang, 2020)
The decision support system (DSS) for employee performance appraisal is a decision support system used in the employee performance appraisal process at PT. Surya Toto Tbk. Currently, the employee performance appraisal process still done manually (paper-based) so that the reports produced were not real-time. From the existing problems, this research aimed to analyze and design a decision support system according to the existing criteria using the Simple Additive Weighting (SAW) method to be able to develop into a Web-based DSS. The method used began with communication with management, especially the perpetrators of employee performance appraisals. Furthermore, planning, the process of data collection, analysis, design, and finally making reports carried out. The conclusion of this study provided a suggestion to use the criteria that had given two more criteria. By giving weights and calculations carried out for three employees, the value obtained for employee C got the highest score (0.98) followed by employee B, and the lowest score (0.85) was employee A.